A Study on the Conservativeness of ISO Standard Fire in Office Buildings. (1st March 2014) - Bahr, Oliver
Abstract : In fire safety engineering, the ISO standard fire often represents fire action. Nevertheless, it is often not clear how conservative the ISO standard fire is when compared to natural fires. Thus, numerical research on fires in office buildings was conducted. To assess the severity of the ISO standard fire, the author proposes a simple approach basing on the heat release rate. For two regarded office rooms, artificial heat release curves were established and used as input in the zone model 'Ozone'. These heat release curves were adjusted in order to match gas temperatures defined by the ISO standard fire. Integration of these curves allows for determining the total energy released by the fire. If this energy is related to the compartment area, it becomes possible to compare the ISO standard fire to natural fires. Results from the limited investigations show that the ISO standard fire becomes more conservative for longer fire duration and that it is quite realistic for offices with moderate opening factors and fire durations of 60 min at most. Contrary, the ISO standard fire tends to be very conservative for offices with higher opening factors.